(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The usage of greater data rates (broader frequency range), propagation in increasingly complicated settings, smart antennas, and multiple-input multiple-output (MIMO) systems are all on the rise in the development of wireless communication. The purpose of this article is to provide a thorough overview of propagation prediction models for terrestrial wireless communication systems. The use of ray-tracing methods to the creation of deterministic propagation models is the subject of this paper, which briefly describes the classic empirical models. It is addressed how to improve computing efficiency and accuracy. Traditional statistical models are also briefly examined to ensure that they are comprehensive. Novel difficulties to propagation prediction are discussed, as well as some new methods for dealing with them. Heinrich Rudolf Hertz discovered the trans- mission of electromagnetic waves in 1886, confirming Maxwell’s long-debated predictions of wave propagation. Guglielmo Marconi, who performed his famous experiments from 1894 to 1901, was the first to achieve the first milestone on the path to wireless communications. In 1901, Marconi showed that a radio wave could maintain communication with ships crossing the English Channel.